Од тоталитарност до виртуелност, од хипертекстуалност до хиперреалност (Филолошки студии, 2019)
In the very beginning of the 21st century, my image of trans-culturalism as a new kind of freedom functioned independently from the political constellations which defined the global changes in the world. My sole orientation was towards letters and sounds, senses and meanings produced by a hypertextual poetics, disregarding the fact that visions persist even in the tacit truths (particularly in totalitarian societies) forming an aperceptive basis of human speech. And this has always been present in the texts which I read: Bakhtin’s, Foucault’s, Derrida’s, and Epstein’s. Thus, I thought that I should not be looking for the meaning of those tacit (or postponed) truths in the articulation (construction) of ideas, but rather in their deconstruction which begins with the authors, and in the reconstruction which continues with the readers, prepared to disseminate their meaning. And so I did, particularly after finding an interesting statement in one of Mikhail Epstein’s essays. It pointed out that there is an analogy between the abbreviations WWW and USSR [originally SSS(R)] which suggests that the history of the creation of the World Wide Web is inscribed in the history of destruction of the former Soviet Union as a chronological continuity, which confirms the thesis for the correspondence between an end and a rise: the end of a powerful totalitarian system and the beginning of a new, virtual one. The following essay is a result of these ideas.